PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA DENGAN TAMPILAN MACROMEDIA FLASH DI SMP - Citrasukmawati, Alfina; Rahardjo, Rahardjo; Tjandrakirana, Tjandrakirana (Universitas Negeri Surabaya, 2012)
The topic Nutrition and Energy Transformation concepts are abstract and difficult to comprehend. To overcome such a difficulty, it is necessary to develop a set of instructional package incorporating Macromedia flash. The Dick and Carey instructional development model was used for that purpose. Before the implementation of the instructional programs, all of the components of the instructional package consisted of lesson implementation plan, media, student worksheet Guided discovery type, student workbook, and assesment intrument, were validated and met the prescribed criteria. Implementation in the school only observe one class without replication. Thirty Junior High School Students involvedin this investigation using One Group Pretest-Postest Design. Result of this research shows the lesson plan is good (3,5), learning modul is good (3,0), student worksheet type Guided discovery is good (3,5), media is good (3,5), and student achievement mastery also good (3,0). Implementation lesson plan in class using direct instruction is good (3,67), with reliability around 82% (good/reliable). Student activity commonly is good (13,25) with reliable average 92%. Student respon is good, above 83%. Student achievement increase with Gain score above 0.7. The result of observation of the teaching and learning process, conducted during its implementation, showed that there was a consistency betweenthe prescribed teaching and learning experienced with its implementation. Students had met the 80% minimum mastery criteria. So it can be concluded that the development instructional package is effective to increase the junior High School student achievement.Â Materi proses perolehan nutrisi dan transformasi energi pada tumbuhan hijau sulit dipahami oleh siswa karena bersifat abstrak, sehingga tidak dapat dilihat secara nyata. Atas dasar itu, perlu kiranya mengembangkan perangkat pembelajaran dengan bantuan tampilan media Macro flash. Untuk itu, telah dilakukan suatu penelitian pengembangan perangkat pembelajaran, yang berorientasi Dick and Carey dan bertujuan meningkatkan hasil belajar siswa. Penelitian ini hanya dilakukan pada satu kelas saja, tanpa melakukan ulangan. Subyek penelitian 30 orang siswa kelas VIII SMP Negeri 22 Surabaya, dengan rancangan Short Case Pretest-Postest, sedangkan analisis data dilakukan secara deskriptif kualitatif. Hasil penilaian RPP baik (3,5), BAS baik (3,0), LKS bercirikan Guided discovery baik (3,5), media baik (3,5) dan tes hasil belajar baik (3,0). Pengelolaan pelaksanaan di kelas dengan pembelajaran langsung termasuk baik (3,67) dengan reliabilitas 82% (baik/reliabel). Aktivitas siswa secara umum baik (13,25)dengan reliabilitas rata-rata 92%. Respon siswa secara umum tertarik sebesar 83% lebih. Tes hasil belajar menunjukan peningkatan tinggi dengan Gain score diatas 0,7. Simpulan penelitian menunjukkan bahwa pengembangan perangkat pembelajaran biologi berbasis Macromedia flash di SMP, layak digunakan, keterlaksanaan pembelajaran, aktivitas dan respon siswa baik, serta dapat meningkatkan hasil belajar siswa.